Modelling and characterisation for the responsive performance of CF/PLA and CF/PEEK smart materials fabricated by 4D printing. Issue 1 (2nd January 2017) - Yang, Chuncheng; Wang, Bingjie; Li, Dichen; Tian, Xiaoyong
ABSTRACT: 4D printing, which is the combination of 3D printing technology and printable smart materials, provides the potential of automating actuation devices. In this paper, we have used a modified-fused deposition modelling 3D printing technology to fabricate a double-layer laminate smart material, which can be activated by temperature directly or by an electric circuit indirectly. A double-layer laminate mathematical model has been developed to describe the bending behaviour caused by the mismatch strain between the surface layer and the basal layer. The electrocaloric deformation testings were performed to find the different bending rules of this low-cost printed active composite in different physical states. The considerable maximal deformation values and deformation force (7 mm and 100 mN for these carbon fibre (CF)/polylactic acid specimens, and 10 mm and 200 mN for these CF/polyether-ether-ketone specimens in the paper) provide this double-layer smart material and 4D printing method the prospective to be applied in biomimetic sensors, actuators, transducers, and artificial muscles.